Navigating the complex landscape of benzodiazepine- and Z-drug diversity: insights from comprehensive FDA adverse event reporting system analysis and beyond - Koniuszewski, Filip; Vogel, Florian D.; Dajić, Irena; Seidel, Thomas; Kunze, Markus; Willeit, Matthäus; Ernst, Margot (Frontiers in Psychiatry, 2023)
Medications which target benzodiazepine (BZD) binding sites of GABAA receptors (GABAARs) have been in widespread use since the nineteen-sixties. They carry labels as anxiolytics, hypnotics or antiepileptics. Many benzodiazepines and several non-benzodiazepine Z-drugs have been marketed to this day. They all share high affinity binding sites on certain subtypes of GABAA receptors, from which they can be displaced by the clinically used antagonist flumazenil. Additional binding sites exist and overlap in part with sites used by some general anesthetics and barbiturates. Despite substantial preclinical efforts, it still remains unclear which receptor subtypes and ligand features mediate individual drug effects. There is a paucity of literature comparing clinically observed adverse effect liabilities across substances in methodologically coherent ways. From both preclinical literature and pharmacovigilance data, there is converging evidence that this very large class of psychoactive molecules displays a broad range of distinctive unwanted effect profiles too broad to be explained by the four canonical, so-called diazepam sensitive high-affinity interaction sites. The substance-specific signatures of compound effects may partly be mediated by phenomena such as occupancy of additional binding sites, and/ or synergistic interactions with endogenous substances like steroids and endocannabinoids. These in turn drive the wanted and unwanted effects and sex differences of individual compounds. In order to examine heterogeneity in outcome, we screened the publicly available U.S. FDA adverse event reporting system (FAERS) database for reports of individual compounds and analyzed them for each sex individually. The complementary use of physico-chemical descriptions of molecules can provide a molecular basis for the analysis of clinical observations of wanted and unwanted drug effects. On the basis of a multifaceted FAERS picture, we suggest that more thorough clinical and pharmacoepidemiological investigations of the heterogenous side effect profiles for benzodiazepines and Z-drugs are needed. This may lead to more differentiated safety profiles and prescription practice for particular compounds, which in turn could potentially ease side effect burden in everyday clinical practice considerably.